An empirical model of aerodynamic drag in Alpine skiing - Elfmark, O.; Bardal, L. M. (Proceedings, 2018)
This paper describes an empirical model of aerodynamic drag for a range of body positions commonly used in alpine skiing. In order to calculate the drag coefficient (CD), a method for calculating the frontal area of an alpine skier, inside a wind tunnel, was used with an uncertainty of 0.012 m2. The general model for aerodynamic drag was based on measurements from one alpine skier. To make the model applicable for athletes of different body sizes and shapes, an investigation of individual adjustments of the model was made, based on measurements of four alpine skiers. The results showed a variation of ±1.4% in the drag coefficient between the different subjects. The frontal area in a reference position was considered a suitable scaling variable. Validations showed an uncertainty of ±3% for the individually adjusted model.